Assessment of prescribing errors reported by community pharmacy professionals - Wudneh Simegn; Berhanemeskel Weldegerima; Mohammed Seid; Ayal Zewdie; Dawit Wondimsigegn; Chilot Abyu; Asmamaw Emagn Kasahun; Abdulwase Mohammed Seid; Gashaw Sisay; Yigizie Yeshaw (Taylor & Francis Group, 2022)
Background Medication errors have serious consequences for patients' morbidity and mortality. The involvement of pharmacy professionals in the prescribing and dispensing procedure allowed the detection of a range of drug-related problems in addition to identification by prescribers. They are often the first point of contact in the healthcare system in identifying prescribing errors and intervening in these errors by dealing with the prescribers and the patients. Objectives This study aimed to assess prescribing errors reported by community pharmacy professionals in Gondar Town, North West Ethiopia. Methods A self-administered cross-sectional survey was employed from February 29 to June 23, 2020, to collect data on prescribing errors reported by community pharmacy professionals. All community pharmacy professionals found in Gondar town were included. Community pharmacy professionals who were ill at the time of study and who had less than 6 months of work experience were excluded. Results Seventy-four pharmacy professionals participated in the study with a response rate of 93.6%. The overall prevalence of prescribing errors was 75.1% (95% CI 71.08-78.70). Of these errors, drug selection was the most common (82.4%), followed by errors of commission (79.7%) and errors of omission (78.4%). Antibiotics (63.5%) were commonly involved in prescribing errors, followed by analgesics (44.5%) and antipsychotics (39.5%). Conclusion The findings of this study revealed a high prevalence of prescribing errors in Gondar, Ethiopia. Drug selection was the most prescribed error, followed by errors of commission. Stakeholders should design interventions such as training, integrating prescribers with clinical pharmacists and supervising interns by seniors. Large-scale studies that include potential factors of prescribing problems are recommended for future researchers.